Decision usefulness of whole-asset operating lease capitalizations - Graham,Roger; King,Raymond (Advances in Accounting, 2013)
Keywords: Accounting

The Value Relevance of Accounting Information During a Financial Crises: Thailand and the 1997 Decline in Value of the Baht - Graham,Roger; King,Raymond; Bailes,Jack (Journal of International Financial Management and Accounting, 2000)
This study addresses whether the financial turmoil surrounding the devaluation of the baht affected the value relevance of Thai accounting information. Our results suggest a decline in the value relevance of Thai book values and earnings following the devaluation. Prior to mid 1997 the Bank of Thailand pegged the value of the baht to a basket of currencies of which 80% was weighted to the US dollar. In response to pressure by currency speculators the bank abandoned its peg on July 2 1997 in favor of a managed float. The devaluation was followed by volatile exchange rates. The change in value relevance of accounting information after the devaluation may be attributable to the initial recognition of foreign exchange losses and the subsequent recognition of foreign exchange gains as exchange rates fell and then recovered.
Keywords: Accounting